Investigating the Effects of Authentic Leadership of Managers on Organizational Commitment of Teachers with Organizational Justice as the Mediator Variable - Alinezhad, Mohsen; Abbasian, Hosein; Behrangi, Mohammad Reza (Ciência e Natura, 2015)
The present study was conducted by the aim of investigating the fit of the presented model for the relationship between authentic leadership and organizational commitment of staff with a mediating role of organizational justice. The population of the research included all the teachers in high schools (for male students) in Education district 2 in Qom city. From the population, 300 individuals were selected through cluster sampling. For gathering the data, authentic leadership questionnaire (Avolio et al., 2007), organizational justice questionnaire of Niehoff & Moorman (1993), and Allen & Meyer's Organizational Commitment Questionnaire (2002) were used. For analyzing the data, structural equation modeling – fit indices and path coefficients – was used. The results of the analysis showed that authentic leadership has a direct and significant effect on the organizational commitment of teachers. Also, authentic leadership has an indirect effect, through organizational justice, on organizational commitment. The other finding of the research is that organizational justice has a direct and significant effect on organizational commitment of teachers, and the offered conceptual model has a significant statistical fit, that means the explanatory model for organizational commitment based on authentic leadership and organizational justice has fitness with empirical data. Finally, based on the information obtained from structural equations model, it can also be said that all the components existing in the 3 variables of the research have positive and significant relationships with one another.